Materials selection and manufacturing of metal membranes for industrial applications - Singh, Himanshu; Saxena, Prateek; Puri, Y. M. (Elsevier, 2020)
In the current scenario, exploration of metal membranes has highly enhanced, and more efforts have been executed in its development and characterization. These breakthroughs have accelerated its applicability in the number of relevant sectors such as waste-water treatments, dairy processing’s, wineries, and biofuel refinement. This short letter inspects about recent findings and progress in the field of metal membranes, including its innovative manufacturing techniques and various applications, which have been reported in multiple research papers. The sintering technique is used generally for the preparation of metal membranes. Throughout this process, the resulting pore sizes are in the range of micrometers. Till now it is used for filtration of liquids to separate the solid particles. There is intense research work required for reducing the pore size of metal membranes using some cost-effective novel techniques, which will intensify its applicability in many green filtration technologies.
Keywords: Porous materials; Metals and Alloy